2015
DOI: 10.1093/europace/euv271
|View full text |Cite
|
Sign up to set email alerts
|

First-line catheter ablation of paroxysmal atrial fibrillation: outcome of radiofrequency vs. cryoballoon pulmonary vein isolation

Abstract: NCT01360008.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
41
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 21 publications
11
41
0
1
Order By: Relevance
“…50 full‐text publications were reviewed, of which 27 were excluded: 19 based on the same cohorts, 6 focused on one type of complication and 2 with data not allowing extraction (Figure S1). 23 studies were finally included in the present systematic review and meta‐analysis …”
Section: Resultsmentioning
confidence: 99%
“…50 full‐text publications were reviewed, of which 27 were excluded: 19 based on the same cohorts, 6 focused on one type of complication and 2 with data not allowing extraction (Figure S1). 23 studies were finally included in the present systematic review and meta‐analysis …”
Section: Resultsmentioning
confidence: 99%
“…Overall, 373 of 4184 (8.9 %) patients were identified as first-line PAF patients undergoing AF ablation. After 1.4 years of follow-up, freedom from AF/atrial tachycardia was similar between RF 61 % and cryoablation 71 %, P = 0.11 [34]. Major events occurred similarly (cryoablation 1.6 % vs RF 3.7 % P = 0.22).…”
Section: Safety Profilementioning
confidence: 80%
“…Previous studies comparing RF ablation with cryoballoon ablation have found comparable results of these two technologies [3][4][5][6][7]. Only a small number of studies showed a higher efficacy of cryoballoon ablation [8][9][10] and a trend for more recurrences and complications in the RF group (probable due to more favorable risk profile in patients undergoing cryoballoon ablation) [11]. In this study, RF ablation has had similar results as cryoballoon ablation at 12 months.…”
Section: Resultsmentioning
confidence: 99%